Design Analysis of a Fish-Shaped PVDF Compliance Microgripper - Neeta Sahay (IAES International Journal of Robotics and Automation (IJRA), 2016)
In this study the design and analysis of compliance microgripper made of piezoelectric PVDF (Poly Vinylidene Fluoride) material is presented. The inverse piezoelectric effect has been used in which the required amount of voltage has been applied at specific points at the base of the structure to produce the force at the tip and thereby the necessary deflection for gripping. The simulated results of frequency response, force-voltage relationship and displacement analysis are presented.